1993
DOI: 10.1111/j.1468-2311.1993.tb00755.x
|View full text |Cite
|
Sign up to set email alerts
|

Criminal Justice Expenditure: A Global Perspective

Abstract: The United Nations Third Survey of Crime and Criminal Justice (United Nations 1987) contains data on global criminal justice expenditure. The data show that between 1982 and 1986 there was a trend of increased expenditure on criminal justice. At the same time crime rates increased. This paper examines criminal justice expenditure in different parts of the system, in an attempt to discover whether there are patterns to global criminal justice expenditure. The author concludes that criminal justice expenditure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Sufficient attention to the meanings embodied in the practices of policing and crime control, will show the shortcomings of such abstractions and this has very real policy implications. Research has already shown that increases in criminal justice expenditure and, by implication, criminal justice reform, tend to answer political and ideological objectives, rather than aiming at feasible criminal justice outcomes and this is true across a great variety of national criminal justice systems (Spencer, 1993). By grounding our understandings of policing and crime control in the manner suggested here, the 'science of police' is less likely to fuel the former and more likely to create a sound basis for the latter.…”
Section: Discussionmentioning
confidence: 97%
“…Sufficient attention to the meanings embodied in the practices of policing and crime control, will show the shortcomings of such abstractions and this has very real policy implications. Research has already shown that increases in criminal justice expenditure and, by implication, criminal justice reform, tend to answer political and ideological objectives, rather than aiming at feasible criminal justice outcomes and this is true across a great variety of national criminal justice systems (Spencer, 1993). By grounding our understandings of policing and crime control in the manner suggested here, the 'science of police' is less likely to fuel the former and more likely to create a sound basis for the latter.…”
Section: Discussionmentioning
confidence: 97%
“…In his analysis of criminal justice expenditure using UNCJS data from the 1980s and performing analysis different from that herein, Jon Spencer (1993) observed: [O]ne country may spend more on the police than another but may not have any more police -it is just that they pay them more. However, this type of distinction is dif cult to make due to de nitional problems of who the police actually are; in some countries the police are included as part of the military.…”
Section: The One-eyed Databasementioning
confidence: 92%
“…The survey has been the primary data source for a number of studies over the years, including those by Nalla and Newman (1994), Harvey et al (1992), Pease (1994), Tseloni and Pease (1994), and Kangaspunta et al (1998aKangaspunta et al ( , 1998b. Jon Spencer (1993) recognized the utility of measuring global expenditure on criminal justice, and a series of studies brought together in a recent publication under the auspices of the United Nations Centre for International Crime Prevention may have proven the utility of the survey to even the most skeptical of its critics (Newman and Howard 1999a, b;Lewis 1999;Mukherjee and Reichel 1999;Shinkai and Zvekic 1999). The UNCJS survey has facilitated unprecedented insights into various aspects of the global criminal justice system.…”
Section: The One-eyed Databasementioning
confidence: 97%